Volume 11: Nano and Micro Materials, Devices and Systems; Microsystems Integration 2011
DOI: 10.1115/imece2011-65001
|View full text |Cite
|
Sign up to set email alerts
|

Performance Degradation of the MEMS Vibratory Gyroscope in Harsh Environments

Abstract: The use of MEMS gyroscopes in a wide range of applications requiring then to function from medium to harsh environments make it necessary to evaluate the performance of MEMS gyroscopes under those conditions. This paper focuses on the effects of elevated temperature and humidity on the performance of MEMS vibratory gyroscopes. Performance of the MEMS gyroscope was evaluated by conducting Highly Accelerated Stress Testing (HAST) on a COTS (commercial-off-the-shelf) single axis MEMS vibratory gyroscope having an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…All the lowfrequency scale coefficients, as well as the wavelet coefficients after threshold processing, is reconstructed by inverse wavelet transform in order to get the estimated value of the original signal. The soft threshold, hard threshold, and soft-hard threshold are three different functions, which are displayed in formulas ( 16), (17), and (18), respectively. In Equation ( 18), the parameters p and q are regulatory factors to obtain a suitable threshold function.…”
Section: B Wavelet Threshold De-noising (Wtd)mentioning
confidence: 99%
See 1 more Smart Citation
“…All the lowfrequency scale coefficients, as well as the wavelet coefficients after threshold processing, is reconstructed by inverse wavelet transform in order to get the estimated value of the original signal. The soft threshold, hard threshold, and soft-hard threshold are three different functions, which are displayed in formulas ( 16), (17), and (18), respectively. In Equation ( 18), the parameters p and q are regulatory factors to obtain a suitable threshold function.…”
Section: B Wavelet Threshold De-noising (Wtd)mentioning
confidence: 99%
“…Joonas Makkonen [16] tested that a 3-axis gyroscope was to be tested under the condition of high relative humidity, and found that the high relative exactly affected the performance of the gyroscope. Chandradip Patel [17] also tested a MEMS gyroscope which under the high relative humidity condition, but they did not propose how to reduce the influence of high relative. It can be concluded that the majority of the existing research focused on the high relative humidity, while fewer optimized the structure of the gyroscope to accuracy its performance.…”
Section: Introductionmentioning
confidence: 99%
“…then both (S1) and (S2) are satisfied. 24 Moreover, the sector-bounded property (8) implies that the following inequality should be considered:…”
Section: Theorem 1 For a Non-linear Gain Function (7)mentioning
confidence: 99%
“…7 Environmental variations and structural defects can degrade the performance of conventional open-loop operation modes for linear momentum regulation, resulting in inaccurate gyroscope outputs. 8 Accordingly, for high performance-demanding applications, a control system is required to guarantee the stability and robustness of the MEMS gyroscope. In recent years, various control methods such as adaptive control, 9,10 sliding mode control, 11 active disturbance rejection control, 12 and model predictive control 13 have been considered for MEMS gyroscopes.…”
Section: Introductionmentioning
confidence: 99%